Implementasi Strategi Employe Engagement Dalam Meningkatkan Retensi Pegawai - Kurniawati, Marenda; Wiharti, Wiharti; Purnamasari, Pupung (Eqien - Jurnal Ekonomi dan Bisnis, 2024)
Institution must has strategies to survive and continue to flourish in today's challenging situation. One important strategy is to strengthen employee engagement as it is a factor that can increase employee retention. The aim of this research is to explain the implementation of initiative employee engagement on Al Binaa IBS. The research uses a qualitative approach. Data collection techniques are conducted through direct observation in the field and interviews with the personnel department. Based on the results of research it is obtained that the employee engagement strategy implemented by Al Binaa has a good impact in improving employee retention. Implementation of employee engagement programmes in Al Binaa includes 1) Employee spiritual building activities; 2) Rewarding staff who perform both work time achievement and staff performance; 3) Benchmarking programmes and regular training; 4) Commonwealth programmes (bonding); 5) Internal communication; 6) Staff well-being.